2020
DOI: 10.3892/ol.2020.11656
|View full text |Cite
|
Sign up to set email alerts
|

Enoxacin inhibits proliferation and invasion of human osteosarcoma cells and reduces bone tumour volume in a murine xenograft model

Abstract: Osteosarcoma is the most prevalent primary bone malignancy in children and adolescents. Neoadjuvant chemotherapy combined with surgical resection, the current standard treatment of osteosarcoma, is associated with a 5-year survival rate of only ~70%. Therefore, it is necessary to identify new, more effective treatment strategies for patients with this lethal disease. Enoxacin is a highly effective broad-spectrum fluoroquinolone antibiotic with low toxicity. The drug inhibits the growth and metastasis of numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Эноксацин является многообещающим средством для лечения некоторых заболеваний, в том числе связанных со старением. Он ингибирует рост многих типов раковых клеток in vitro и in vivo, включая остеосаркому [36], меланому [37], рак предстательной железы [26], поджелудочной железы [38], легкого [39], щитовидной железы [40], шейки матки [41]. Кроме того, это вещество останавливает прогрессирование аутоиммунного процесса в тканях желчевыводящих путей [42], а также уменьшает вызванное диетой (с высоким содержанием жиров 60 %) ожирение у мышей, нормализует уровень глюкозы в крови и снижает симптомы бокового амиотрофического склероза [43,44].…”
Section: анализ продолжительности жизниunclassified
“…Эноксацин является многообещающим средством для лечения некоторых заболеваний, в том числе связанных со старением. Он ингибирует рост многих типов раковых клеток in vitro и in vivo, включая остеосаркому [36], меланому [37], рак предстательной железы [26], поджелудочной железы [38], легкого [39], щитовидной железы [40], шейки матки [41]. Кроме того, это вещество останавливает прогрессирование аутоиммунного процесса в тканях желчевыводящих путей [42], а также уменьшает вызванное диетой (с высоким содержанием жиров 60 %) ожирение у мышей, нормализует уровень глюкозы в крови и снижает симптомы бокового амиотрофического склероза [43,44].…”
Section: анализ продолжительности жизниunclassified
“…As shown in Table 1, in vitro and in vivo investigations on various types of cancer using several members of this family of antibiotics have shown a signi cant inhibitory effect on cancer cell growth and proliferation. Among all uoroquinolones tested, enoxacin has frequently been found to have the most potent inhibitory effect on cancer cells 12,13 . It was revealed that the anti-cancer effects of enoxacin is exerted through the general enhancement of the RNA interference (RNAi) pathway, thereby stimulating the miRNA biogenesis pathway 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is widely acknowledged as the most common type of primary malignant bone tumor that arises from mesenchymal tissue, 1 with an incidence rate of 4 to 5 cases per million people. 2 It has a bimodal age distribution pattern, occurring predominantly in children and young adults <20 years of age and those >50-60 years of age. 3,4 It has been reported that metastasis disease is found in approximately 20% of osteosarcoma patients at diagnosis.…”
Section: Introductionmentioning
confidence: 99%